Managing drainagbe and irrigation case of Chambal, Rajasthan Cad and Rajad projects / edited by Rakesh Hooja, N. A. Visvanatha and S. N. Mundra - Hooja, Rakesh (ed.) (New Delhi, 1997)
The book is a compilation of papers closely linked with the experience during the period 1960 to 1996of the command area development authority (CADA) in the development and management of drainage and irrigation system in chambal command area(CA) in the state of rajasthan india.
Keywords: Drainage